A Comparative Analysis Of Tripartite Political Psychology In Plato And Freud - Küçükseymen, Zeynep Cansu (Institute of Social Sciences, 2019)
This thesis examines the political psychologies of Plato and Freud in terms of their similarities and dissimilarities, and argues that there are both advantages and limitations of doing political theory using psychological analysis. The first chapter explains the aim of this thesis, which is to compare the tripartite political psychologies in Plato's Republic and Freud's Civilization and its Discontents. The second chapter gives a detailed account of the city and the soul in the Republic focusing on Books II-IV and offering a review of different interpretations of the parts of the mind and city-soul analogy. The third chapter starts with clarifications of several important concepts in Psychoanalysis before moving on to a thorough explanation of Civilization and its Discontents and a review of different interpretations of the topics discussed. The fourth chapter examines similarities and dissimilarities of the tripartition of the mental life and analogies between the individual mind and society in both accounts. It addresses several points of contribution of psychoanalytic concepts to understanding the mechanisms of self-knowledge that can resume a Platonic approach to developing a strong virtuous and happy life. The last chapter discusses the limitations and advantages of basing political analysis on psychological investigation.

Bu tez Platon ve Freud'un politik psikolojilerini benzerlikleri ve farklılıkları açısından inceleyerek ve psikolojik analiz kullanarak siyaset teorisi yapmanın hem avantajları hem de sınırlamaları olduğunu savunuyor. İlk bölüm bu tezin amacını açıklamaktadır. Tezin amacı Platon'un Devlet ve Freud'un Uygarlığın Huzursuzluğu kitaplarındaki üçlü politik psikolojileri karşılaştırmaktır. İkinci bölüm, özellikle ikinci ve dördüncü kitaplara odaklanarak Devlet kitabındaki şehir ve ruhun ayrıntılı bir açıklamasını vermektedir, ayrıca zihin ve şehir-ruh analojisi bölümlerinin farklı yorumlarının incelenmesini de içerir. Üçüncü bölüm, Uygarlığın Huzursuzluğu kitabını ayrıntılı bir şekilde açıklanmasına ve tartışılan konuların farklı yorumlarının gözden geçirilmesine geçmeden önce Psikanalizdeki birkaç önemli kavramın açıklanması ile başlamaktadır. Dördüncü bölüm, her iki kuramda zihinsel yaşamın üçlü bölümünün benzerliği ve farklılıkları ile bireysel zihin ile toplum arasındaki analojileri incelemektedir. Ayrıca Psikanalitik kavramların, Platonik yaklaşımı devam ettirebilecek güçlü, erdemli ve mutlu bir yaşam geliştirmeye devam edebilecek öz farkındalık mekanizmalarını anlamadaki birkaç katkısını ele almaktadır. Son bölümde ise siyasi analizin psikolojik araştırmalara dayandırılmasının sınırlamaları ve avantajları tartışılmaktadır.
Platon Ve Freud'un İç Parçalı Politik Psikolojilerinin Karşılaştırmalı Analizi
Thesis (M.A) -- İstanbul Technical University, Institute of Social Sciences, 2019
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Philosophy; Political Science; Felsefe; Siyasal Bilimler